Ethnography of past happiness. Work in the yeast factory in Maszewo Lęborskie: English - Busz, Jakub (LUD. Organ Polskiego Towarzystwa Ludoznawczego, 2024)
For inhabitants of Maszewo Lęborskie, the memory of work in the yeast factory is an important point on which their local community is based. It is a memory of a strong integrating feature that unites the people of Maszewo. The workers’ lifestyle, shaped by the yeast factory after its collapse, was transformed into a community of memories. I present an outline of the history of the yeast factory in Maszewo and created examples of the discourse of memory around it.